Constitutional Analysis of Central–Regional Government Authority Relations in Indonesia - Iskandar Syukur (Publica: Jurnal Pemikiran Administrasi Negara, 2026)
The relationship of authority between the central and regional governments remains a constitutional issue in Indonesia due to continuing changes in regional government legislation and persistent conflicts in the implementation of concurrent governmental affairs, particularly in natural resource management, spatial planning, infrastructure development, environmental governance, and business licensing. While post-reform decentralization expanded regional autonomy, subsequent regulatory reforms have also strengthened national coordination, creating challenges in defining the limits of governmental authority. This study analyzes the constitutional framework and regulatory evolution governing central–regional authority relations in the Unitary State of the Republic of Indonesia while offering a comparative analysis of successive regional government laws to explain the shift in the distribution of governmental authority. Employing normative legal research, the study adopts statutory, conceptual, and comparative approaches by examining the 1945 Constitution of the Republic of Indonesia, Law No. 22 of 1999, Law No. 32 of 2004, Law No. 23 of 2014, Law No. 1 of 2022, and relevant legal literature. The findings demonstrate a regulatory shift from centralized governance toward broad decentralization and subsequently toward stronger national coordination through a more structured allocation of governmental affairs. The comparative analysis further reveals that although the constitutional framework provides a clear legal basis for regional autonomy, overlapping authority, inconsistent interpretation of concurrent affairs, and coordination problems continue to generate legal uncertainty across strategic sectors. These findings contribute by clarifying the constitutional evolution of authority allocation in Indonesia and suggest the need to harmonize sectoral legislation with the Regional Government Law, strengthen transitional arrangements following regulatory reforms, and establish clearer institutional coordination mechanisms to improve legal certainty and governance effectiveness.